ASEAN’s External Economic Relations and the Limits of Its Economic Diplomacy - Pantri Muthriana Erza Killian (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2022)
The purpose of this article is to outline the multiple facets of ASEAN’s external economic relations (EER), loosely termed as ASEAN economic diplomacy. In doing so, this article builds on two main frameworks: strands of economic diplomacy and general framework of economic diplomacy and employs research interviews and documentary analysis as the main research method. Findings suggest that ASEAN is most advanced in its trade diplomacy, relying on the ASEAN-plus scheme. ASEAN also displays an interesting pattern in their trade diplomacy, since it is mostly aimed at achieving political goals rather than economic ones. The main reason for this is because ASEAN member states can actually achieve larger economic gains by negotiating individually rather than collectively through ASEAN. However, ASEAN still faces limitations in doing collective negotiations due to its regional development gap, different levels of economic ambition, absence of a common external tariff and the lack of a regional negotiator acting on behalf of ASEAN. Keywords: ASEAN, economic diplomacy, external economic relations, trade diplomacy